2020
DOI: 10.1111/vru.12943
|View full text |Cite
|
Sign up to set email alerts
|

Early radiation‐induced oral pain signaling responses are reduced with pentoxifylline treatment

Abstract: Radiation‐induced acute oral mucositis is associated with inflammation and pain. In other realms of pain research, nociceptors are known to be activated by inflammatory cytokines; for example, tumor necrosis factor alpha (TNF‐α) can activate transient receptor potential ion channels on sensory neurons. But there is an unclear relationship between inflammatory cytokines and molecular mediators of pain in radiation‐induced mucositis (RIM) and radiation‐associated pain (RAP). In this prospective, analytical, expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…PTX can also decrease the risk of radiation-induced oral mucositis after oral administration. In an experimental pilot study, PTX suppressed TNF receptor upregulation and neuronal responsiveness in patients with RTOM ( 55 ). Similarly, radiotherapy combined with PTX and vitamin E reduced the incidence of severe oral mucositis and dysphagia after adjusting for age ( 56 ).…”
Section: Strategies To Reduce Radiation Injurymentioning
confidence: 99%
“…PTX can also decrease the risk of radiation-induced oral mucositis after oral administration. In an experimental pilot study, PTX suppressed TNF receptor upregulation and neuronal responsiveness in patients with RTOM ( 55 ). Similarly, radiotherapy combined with PTX and vitamin E reduced the incidence of severe oral mucositis and dysphagia after adjusting for age ( 56 ).…”
Section: Strategies To Reduce Radiation Injurymentioning
confidence: 99%
“…Ptx has been marketed for other purposes such as leprosy ( Legendre et al, 2012 ). Ptx has been tested in several preclinical rodent models of neuropathic pain, such as chemotherapy, chronic constriction injury, and spinal nerve transection ( Liu et al, 2007 ; Mika et al, 2007 ; Kim et al, 2016 ); inflammatory pain ( Vale et al, 2004 ); radiation-induced pain ( Price et al, 2021 ); and bone fracture–induced complex regional pain syndrome ( Wei et al, 2009 ). Ptx has also shown positive effects in the treatment of human lumbar disc herniation–induced radicular pain ( Tarabay et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the combination of PTX and vitamin E (7) reduces the severity of radiation-induced oral mucositis and dysphagia in head and neck cancer patients (8,9). In addition, it has been suggested that PTX reduces chemotherapy-induced stomatitis and osteonecrosis, through inflammatory cytokine reduction (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%